2015
DOI: 10.1371/journal.pone.0132845
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Modulates Pancreatic Adenocarcinoma Cell-Derived Exosomal Function

Abstract: Pancreatic cancer has the highest mortality rates of all cancer types. One potential explanation for the aggressiveness of this disease is that cancer cells have been found to communicate with one another using membrane-bound vesicles known as exosomes. These exosomes carry pro-survival molecules and increase the proliferation, survival, and metastatic potential of recipient cells, suggesting that tumor-derived exosomes are powerful drivers of tumor progression. Thus, to successfully address and eradicate panc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(78 citation statements)
references
References 57 publications
2
68
0
1
Order By: Relevance
“…Hence, exosomes containing curcumin could be employed as a new option for the treatment of pancreatic cancer (Osterman et al, 2015).…”
Section: Curcumin and Exosome In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, exosomes containing curcumin could be employed as a new option for the treatment of pancreatic cancer (Osterman et al, 2015).…”
Section: Curcumin and Exosome In Cancermentioning
confidence: 99%
“…This finding may indicate that exosomes containing curcumin could improve efficacy of curcumin against pancreatic cancer cells. Hence, exosomes containing curcumin could be employed as a new option for the treatment of pancreatic cancer (Osterman et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The efficacy of curcumin-containing exosomes in vivo was also tested using H1299 cells injected into nude mice, followed by either curcumin (300 mg/kg) or exosome daily for 24 days; the curcumintreated mice showed significantly higher TCF21 expression than those treated with vehicle (Wu et al, 2016). (Osterman et al, 2015). Collectively, these data suggest that the efficacy of curcumin as an anticancer and anti-inflammatory agent may be promoted in pancreatic cancer cells through exosomes.…”
Section: Impact Of Curcumin On Proinflammatory Cytokine Gene Expresmentioning
confidence: 93%
“…The use of exosomes as drug delivery vehicles has gained considerable interest due to their excellent biodistribution and biocompatibility [81], which should enhance the stability and specificity, and reduce the side effects and immunogenic response, of therapeutic agents. Indeed, Osterman et al showed that exosome-bound curcumin is readily taken up by cultured PDAC cells and is effective in inducing cytotoxicity [82]. Moreover, Pascucci et al demonstrated that mesenchymal stromal cell-derived exosomes can effectively deliver active drugs, such as paclitaxel, to inhibit tumor growth [83].…”
Section: Exosomes As Drug Delivery Vehiclesmentioning
confidence: 99%